Preparation method and application of bimetallic Cu / Ni / C-S composite material applied to room-temperature sodium-sulfur battery positive electrode

By preparing a bimetallic Cu/Ni/CS composite material as the cathode for a room-temperature sodium-sulfur battery, the problems of polysulfide shuttle effect and poor cycle stability were solved, thereby improving the reaction kinetics and cycle performance of the battery.

CN119284873APending Publication Date: 2025-01-10HEFEI UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411381468.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Existing room temperature sodium-sulfur batteries suffer from polysulfide shuttle effect, poor cycle stability, and severe sulfur volume expansion, resulting in poor battery performance.

Method used

Bimetallic Cu/Ni/CS composite material was used as the cathode material and prepared by chemical deposition, high-temperature calcination and melt diffusion methods. The distribution of sulfur was optimized by combining it with three-dimensional MOF material to enhance reactivity, and transition metal catalysis was used to accelerate reaction kinetics.

Benefits of technology

It effectively inhibits the dissolution of polysulfides, shortens the transport path of sodium ions, improves the cycle performance and rate performance of the battery, and achieves excellent electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119284873A_ABST
    Figure CN119284873A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a bimetallic Cu / Ni / C-S composite material applied to a room-temperature sodium-sulfur battery positive electrode, and relates to the technical field of new energy material preparation. The bimetallic Cu / Ni / C-S composite material prepared by adopting a chemical deposition method, a high-temperature calcination method and a melt diffusion method in sequence is good in homogeneity, the three-dimensional structure of the bimetallic Cu / Ni / C-S composite material is composed of nanocubes with the average length being 200 nm, the specific surface area is large, multiple internal exposed atomic sites can be achieved, sulfur distribution can be optimized, the reactivity of the bimetallic Cu / Ni / C-S composite material can be enhanced, and the service life of the bimetallic Cu / Ni / C-S composite material is prolonged. The transmission path of sodium ions can be shortened; rich micropore and mesoporous structures on the nano cube are beneficial to diffusion of confinement sulfur and electrolyte; meanwhile, the bimetallic copper-nickel has a relatively strong chemical adsorption effect on polysulfide, and can catalyze conversion of the polysulfide, effectively inhibit dissolution of the polysulfide, accelerate reaction kinetics and shorten a transmission path of sodium ions, so that the room-temperature sodium-sulfur battery with excellent electrochemical performance is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new energy material preparation, and in particular to a preparation method and application of a bimetallic Cu / Ni / CS composite material for a positive electrode of a room temperature sodium-sulfur battery. Background Art

[0002] As the energy demand of electronic and electrical equipment continues to grow, traditional lithium-ion batteries can no longer meet the demand. Room temperature sodium-sulfur batteries (RT Na-S batteries) have attracted much attention due to their abundant raw materials, low prices, environmental friendliness, and high capacity density, becoming a potential alternative for large-scale energy storage applications. Although research on room temperature Na-S batteries began in the 1980s, global research interest in room temperature Na-S batteries peaked in the past decade. With the in-depth study of its predecessor, lithium-sulfur batteries (Li-S batteries), many problems in Na-S battery research have also been improved, including volume expansion, severe shuttle effect, and rapid capacity decay.

[0003] At present, the strategy to improve the conductivity of room temperature Na-S batteries is mainly to improve the interface charge transfer rate of sulfides by compounding with conductive substrate materials (such as carbon materials), improving the morphology and structure of sulfides, using catalysts to improve their cycle performance, and designing battery structures, thereby improving their conductivity, promoting rapid electron conduction and shortening the Na + Therefore, room temperature sodium-sulfur batteries are considered to be the most promising candidates for the next generation of energy storage systems.

[0004] However, the shortcomings of sodium polysulfide shuttle effect, poor cycle stability, and severe sulfur volume expansion in sodium-sulfur batteries hinder their practical application. In response to the problems of the above-mentioned sodium-sulfur batteries, researchers have actively explored and improved them. The main existing solution strategy is to use different types of conductive carbon materials (such as carbon nanotubes, carbon hollow spheres, and porous carbon, etc.) as sulfur-carrying materials to composite with active sulfur materials, thereby improving the conductivity of the sulfur positive electrode. Chinese patent application CN 116553520A discloses "Preparation of a high-performance room temperature sodium-sulfur battery positive electrode material", using high-specific surface area biomass carbon after high-temperature calcination as a sulfur carrier. The synthesis steps of this freeze-drying and heat-treatment carbonization are relatively complicated. In addition, the material prepared in the above manner is large in size, the electrochemical activity of sulfur cannot be effectively utilized, and the polysulfide shuttle effect can only be reduced by the adsorption of the porous carbon matrix, which is limited, resulting in poor battery cycle performance.

[0005] To this end, the present invention proposes an application of a bimetallic MOF material as a positive electrode material for a room temperature sodium-sulfur battery. The selection of a three-dimensional structured MOF material can optimize the distribution of the active substance sulfur, enhance its reactivity, shorten the transfer path of sodium ions, and accelerate the reaction rate; and integrating transition metals copper and nickel as heteroatoms into the carbon skeleton can catalyze and accelerate the Na2S n The conversion reaction kinetics can also improve the adsorption capacity of polar components on the matrix. Summary of the invention

[0006] In view of the problems in the prior art, the purpose of the present invention is to provide a method for preparing a bimetallic Cu / Ni / CS composite material for a room temperature sodium-sulfur battery positive electrode, and apply the prepared bimetallic Cu / Ni / CS composite material to a room temperature sodium-sulfur battery, which can not only effectively solve the polysulfide shuttling, but also improve the problem of slow reaction kinetics of room temperature sodium-sulfur batteries.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is:

[0008] A method for preparing a bimetallic Cu / Ni / CS composite material for a room temperature sodium-sulfur battery positive electrode comprises the following steps:

[0009] (1) dispersing 2-methylimidazole in deionized water to obtain a mixture A; dissolving zinc nitrate hexahydrate, copper nitrate trihydrate, and nickel nitrate hexahydrate in deionized water to obtain a mixture B; and dissolving hexadecyltrimethylammonium bromide in deionized water to obtain a mixture C;

[0010] (2) slowly adding mixture C to mixture A, and then slowly adding mixture B, sealing and performing chemical deposition reaction at room temperature, and after the reaction is completed, centrifuging the product, washing, and drying to obtain a Zn / Cu / Ni-MOF precursor;

[0011] (3) Under the protection of inert gas, the Zn / Cu / Ni-MOF precursor is calcined at high temperature to obtain a bimetallic copper-nickel doped cubic porous carbon material Cu / Ni@C;

[0012] (4) The bimetallic copper-nickel doped cubic porous carbon material Cu / Ni@C is mixed with sulfur powder and placed in a reactor for melt diffusion reaction to obtain a bimetallic Cu / Ni / CS composite material.

[0013] As a further preferred technical solution of the present invention, in the preparation method:

[0014] In the step (1), the mass ratio of 2-methylimidazole, zinc nitrate hexahydrate, copper nitrate trihydrate, nickel nitrate hexahydrate and hexadecyltrimethylammonium bromide is 0.1-0.5:10-15:1:1:0.1-0.5.

[0015] The temperature of the room temperature reaction in step (2) is 0 to 40° C., and the reaction time is 3 to 6 hours.

[0016] In the step (3), the high temperature calcination temperature of the Zn / Cu / Ni-MOF precursor is 950-1100°C, and the calcination time is 3-8h. The Zn / Cu / Ni-MOF precursor is heated to a specified calcination temperature at a heating rate of 0.1-10°C / min. The inert gas is a gas that does not react with the Zn / Cu / Ni-MOF precursor and carbon. Specifically, argon, helium, and helium / argon mixed gases commonly used in the art can be selected.

[0017] In the step (4), the mass ratio of the bimetallic copper-nickel doped cubic porous carbon material Cu / Ni@C to the sulfur powder is 1: 1. The reaction temperature of the melt diffusion method is 155-165° C., and the reaction time is 12-24 hours.

[0018] The second object of the present invention is to provide a bimetallic Cu / Ni / CS composite material obtained according to the aforementioned preparation method.

[0019] The third object of the present invention is to provide the use of the aforementioned bimetallic Cu / Ni / CS composite material as a positive electrode material for room temperature sodium-sulfur batteries.

[0020] The beneficial effects of the present invention are specifically shown as follows:

[0021] 1. The present invention uses 2-methylimidazole, copper nitrate trihydrate, nickel nitrate hexahydrate, zinc nitrate hexahydrate, and hexadecyltrimethylammonium bromide as raw materials, and adopts chemical deposition method, high temperature calcination method and melt diffusion method to prepare bimetallic Cu / Ni / CS composite material, and its preparation process is simple, the reaction conditions are mild, and the cost is low.

[0022] 2. The present invention can control the morphology of the obtained bimetallic Cu / Ni / CS composite material by adjusting the process conditions such as reaction temperature, pyrolysis temperature, heating rate and reactant ratio. The prepared bimetallic Cu / Ni / CS composite material has good uniformity, and its three-dimensional structure is composed of nanocubes with an average length of 200nm, with a large specific surface area and many exposed atomic sites inside, which can not only optimize the distribution of sulfur and enhance its reactivity, but also shorten the transmission path of sodium ions; and the rich micropores and mesoporous structures contained in the nanocubes are conducive to the diffusion of confined sulfur and electrolyte; at the same time, the bimetallic copper and nickel have a strong chemical adsorption effect on polysulfides, can catalyze the conversion of polysulfides, effectively inhibit the dissolution of polysulfides, accelerate the reaction kinetics, and shorten the transmission path of sodium ions, thereby obtaining a room temperature sodium-sulfur battery with excellent electrochemical performance.

[0023] 3. The bimetallic Cu / Ni / CS composite material prepared by the present invention can be applied in the fields of energy storage and catalysis. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 X-ray diffraction patterns of C material prepared without doping with metal elements, bimetallic copper-nickel doped cubic porous carbon material Cu / Ni@C prepared in Example 1 of the present invention, and bimetallic Cu / Ni / CS composite material.

[0025] Figure 2 This is a scanning electron microscope image of the Zn / Cu / Ni-MOF precursor material prepared in Example 1 of the present invention.

[0026] Figure 3 This is a scanning electron microscope image of the bimetallic Cu / Ni / CS composite material prepared in Example 1 of the present invention.

[0027] Figure 4 The nitrogen adsorption-desorption isotherm and pore size distribution diagram of the bimetallic copper-nickel doped cubic porous carbon material Cu / Ni@C prepared in Example 1 of the present invention.

[0028] Figure 5 The Cu / Ni / CS composite material prepared in Example 1 of the present invention is used as a positive electrode material for a room temperature sodium-sulfur battery at 0.1, 0.2, 0.5, 1, and 2 Ag. -1 The following rate performance diagram.

[0029] Figure 6 The Cu / Ni / CS composite material prepared in Example 1 of the present invention is used as a positive electrode material for a room temperature sodium-sulfur battery at 0.5Ag -1 Cycling performance diagram at different current densities. DETAILED DESCRIPTION

[0030] The present invention is further described in detail below in conjunction with embodiments and drawings.

[0031] Example 1

[0032] (1) 10.8 g of 2-methylimidazole was dissolved in 130 mL of deionized water to obtain a mixture A. 700 mg of zinc nitrate hexahydrate, 50 mg of copper nitrate hexahydrate, and 50 mg of nickel nitrate trihydrate were dissolved in 70 mL of deionized water to obtain a mixture B. 16.2 mg of hexadecyltrimethylammonium bromide was added to 4.4 mL of deionized water and subjected to ultrasonic dispersion for 15 min to obtain a mixture C.

[0033] (2) Add mixture A to a beaker, stir and mix at a speed of 700 r / min and a temperature of 25°C for 15 minutes, then slowly add mixture C dropwise, and then slowly add mixture B dropwise after mixture C is added dropwise. After mixture B is added dropwise, seal the beaker with a plastic film and keep it warm at room temperature for 6 hours; after the reaction is completed, age at room temperature for 3 hours, collect the reaction product and centrifuge it at a speed of 9000 rpm for 5 minutes to separate the mother liquor to obtain a crude product; wash with deionized water and centrifuge to collect the product, repeat this process 3 times, then wash once with ethanol and centrifuge to collect the final product; place the final product in a vacuum drying oven at 100°C and dry it for 12 hours to obtain a Zn / Cu / Ni-MOF precursor.

[0034] (3) The Zn / Cu / Ni-MOF precursor prepared in step (2) is loaded into a porcelain boat, and the porcelain boat is placed in a well-sealed tubular furnace. Under the protection of an argon atmosphere, the temperature is increased to 950°C at a heating rate of 5°C / min and kept for 3 hours. The mixture is naturally cooled to room temperature to obtain a bimetallic copper-nickel doped cubic porous carbon material Cu / Ni@C.

[0035] (4) The bimetallic copper-nickel doped cubic porous carbon material Cu / Ni@C prepared in step (3) was mixed with sulfur powder in a mass ratio of 1:1, and then placed in a 5 mL reactor under the protection of an argon atmosphere in a glove box, placed in a drying oven, heated to 160°C, and kept warm for 12 h. The mixture was naturally cooled to room temperature in the furnace to obtain a bimetallic Cu / Ni / CS composite material.

[0036] For comparison, copper nitrate hexahydrate and nickel nitrate trihydrate were omitted in the above step (1), thereby preparing a C material without doping with metal elements. X-ray diffraction analysis was performed together with the bimetallic copper-nickel doped cubic porous carbon material Cu / Ni@C and the bimetallic Cu / Ni / CS composite material prepared in Example 1.

[0037] from Figure 1 It can be seen that the diffraction peak spectrum of the bimetallic copper-nickel doped cubic porous carbon material Cu / Ni@C prepared in Example 1 contains the diffraction peak of carbon and three characteristic peaks of copper and nickel, indicating the successful doping of copper and nickel; while after sulfur loading, only the diffraction peak of amorphous carbon exists, and no surface sulfur exists, indicating that sulfur exists in the form of amorphous sulfur rather than crystalline sulfur, and crystalline sulfur is more easily dissolved in the electrolyte to cause polysulfide shuttling.

[0038] from Figure 2 It can be seen that the microstructure of the Zn / Cu / Ni-MOF precursor material prepared in Example 1 is composed of single nanocubes (average length of about 200 nm).

[0039] from Figure 3It can be seen that the morphology of the precursor material did not change significantly after carbonization and sulfur loading, and still maintained a cubic shape.

[0040] from Figure 4 It can be seen that the specific surface area of ​​the bimetallic copper-nickel doped cubic porous carbon material Cu / Ni@C prepared in Example 1 is 1048.7 m 2 / g, and the pore size distribution is about 1.5nm.

[0041] Example 2

[0042] The bimetallic Cu / Ni / CS composite material prepared in Example 1 was used as the positive electrode material of the room temperature sodium-sulfur battery, mixed with carbon black Super P and PVDF (polyvinylidene fluoride) in a mass ratio of 7:2:1, and an appropriate amount of NMP (N-methylpyrrolidone) was added dropwise. The mixed slurry was ball-milled to form a mixed slurry, which was then evenly coated into a pole piece, and then dried in a vacuum oven at 80°C for 12 hours. The dried pole piece was roll-pressed and cut into a circular pole piece with a diameter of 12 mm.

[0043] The room temperature sodium sulfur battery was assembled in a glove box filled with argon. The electrolyte was sodium perchlorate with a concentration of 1 mol / L. The electrolyte was ethylene carbonate and propylene carbonate with a volume ratio of 1:1 and 5% ethylene fluoride carbonate. The metal sodium sheet was used as the counter electrode. The diaphragm was glass fiber (Whatman GF / D). The button battery shell used CR2025. The electrochemical performance test was carried out on the LAND system, and the battery charge and discharge voltage range was 0.8 to 2.8V.

[0044] Result analysis:

[0045] from Figure 5 It can be seen that the specific capacity of the Cu / Ni / CS composite material has almost no decay after 5 cycles at different current densities. -1 When the reversible specific capacity is still comparable to that at the beginning of 0.1A -1 The 5-cycle specific capacity is close to that of the control samples Cu / CS and pure CS, and the rate performance of the Cu / Ni / CS composite material is significantly better than that of the control samples Cu / CS and pure CS, indicating that the Cu / Ni / CS composite material prepared in this application has excellent rate performance when applied to room temperature sodium-sulfur batteries.

[0046] from Figure 6 It can be seen that at 1Ag -1 At a current density of 1.5 Å, the first-cycle reversible specific capacity of the Cu / Ni / CS composite material is 1639.4 mAh / g, and the coulombic efficiency is 61.2%. After 400 cycles, the reversible specific capacity can be maintained at 623.6 mAh / g, and the coulombic efficiency is close to 100%. This is significantly better than 1Ag -1Compared with the Cu / CS material and CS material at a current density of , their first-cycle reversible specific capacities were 1384.2 mAh / g and 1365.7 mAh / g, respectively, and their coulombic efficiencies were 58% and 54%. After 400 cycles, the reversible specific capacities were only 432.5 mAh / g and 374.8 mAh / g.

[0047] In summary, the room temperature sodium-sulfur battery assembled using the bimetallic Cu / Ni / CS composite material described in this application as the positive electrode material improves the NaPS conversion reaction kinetics by utilizing the catalytic effect of bimetallic nanoparticles and improves the soluble polysulfide shuttle effect of sulfur during the cycle, thereby obtaining excellent rate performance and cycle stability.

[0048] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A method for preparing a bimetallic Cu / Ni / CS composite material for a room temperature sodium-sulfur battery positive electrode, characterized in that: The following steps are involved: (1) dispersing 2-methylimidazole in deionized water to obtain a mixture A; dissolving zinc nitrate hexahydrate, copper nitrate trihydrate, and nickel nitrate hexahydrate in deionized water to obtain a mixture B; and dissolving hexadecyltrimethylammonium bromide in deionized water to obtain a mixture C; (2) slowly adding mixture C to mixture A, and then slowly adding mixture B, sealing and performing chemical deposition reaction at room temperature, and after the reaction is completed, centrifuging the product, washing, and drying to obtain a Zn / Cu / Ni-MOF precursor; (3) Under the protection of inert gas, the Zn / Cu / Ni-MOF precursor is calcined at high temperature to obtain a bimetallic copper-nickel doped cubic porous carbon material Cu / Ni@C; (4) The bimetallic copper-nickel doped cubic porous carbon material Cu / Ni@C is mixed with sulfur powder and placed in a reactor for melt diffusion reaction to obtain a bimetallic Cu / Ni / CS composite material.

2. The preparation method according to claim 1, characterized in that In the step (1), the mass ratio of 2-methylimidazole, zinc nitrate hexahydrate, copper nitrate trihydrate, nickel nitrate hexahydrate and hexadecyltrimethylammonium bromide is 0.1-0.5:10-15:1:1:0.1-0.

5.

3. The preparation method according to claim 1, characterized in that: The temperature of the room temperature reaction in step (2) is 0 to 40° C., and the reaction time is 3 to 6 hours.

4. The preparation method according to claim 1, characterized in that: In the step (3), the high temperature calcination temperature of the Zn / Cu / Ni-MOF precursor is 950-1100° C., and the calcination time is 3-8 hours.

5. The preparation method according to claim 4, characterized in that: In the step (3), the Zn / Cu / Ni-MOF precursor is heated to a specified calcination temperature at a heating rate of 0.1 to 10°C / min.

6. The preparation method according to claim 1, 4 or 5, characterized in that: The inert gas in step (3) is a gas that does not react with the Zn / Cu / Ni-MOF precursor and carbon.

7. The preparation method according to claim 1, characterized in that: In the step (4), the mass ratio of the bimetallic copper-nickel doped cubic porous carbon material Cu / Ni@C to the sulfur powder is 1:

1.

8. The preparation method according to claim 1, characterized in that: In the step (4), the reaction temperature of the melt diffusion method is 155-165° C., and the reaction time is 12-24 hours.

9. The bimetallic Cu / Ni / CS composite material prepared by the method according to any one of claims 1 to 8.

10. Use of the bimetallic Cu / Ni / CS composite material as claimed in claim 9 as a positive electrode material for room temperature sodium-sulfur batteries.

Citation Information

Patent Citations

  • Preparation method and application of high-performance room-temperature sodium-sulfur battery positive electrode material

    CN116553520A